Inclusive learning strategies for students with intellectual disabilities in East Kalimantan: A case study in primary education - Bahri, Saipul; Mumpuniarti, Mumpuniarti (Jurnal Penelitian Ilmu Pendidikan, 2025)
This study investigates the implementation of inclusive learning strategies for students with intellectual disabilities at SD Negeri 009 Sangkulirang East Kalimantan, Indonesia, using a qualitative descriptive approach. Data collected through observations, interviews, and document analysis reveals that teachers' readiness for inclusive education is limited, necessitating further training and support. Key challenges include insufficient resources, professional development, and time for designing effective strategies. Multisensory and individualized instructional methods are found to be more effective compared to traditional approaches. Additionally, visual aids and educational technology enhance student participation. Although the school has made efforts to provide supportive facilities, these are not yet optimal. It is vital to strengthen parental and community involvement to create more inclusive environment. The study underscores the need for clear school policies supporting inclusive education, ongoing teacher training, and adequate resource allocation. The curriculum should be flexible to accommodate the needs of students with intellectual disabilities while upholding educational standards. Recommended strategic initiatives include developing teacher training modules, fostering collaboration with inclusive education experts, and optimizing the use of technology and adaptive learning tools.